Cultural Translation Strategies of Cultural Elements in the English Version of Gadis Kretek: Translating Indonesian Cultural Nuances - rafikah Hasibuan; Meida Rabia Sihite; Sofia Idawati Lubis (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2026)
This research explores the cultural translation strategies employed in the English version of Ratih Kumala’s novel Gadis Kretek, which was translated by Annie Tucker as Cigarette Girl. Translating a literary work that is deeply embedded in Indonesian culture presents unique challenges, particularly in maintaining cultural authenticity while ensuring that the text remains accessible and comprehensible to international readers. Guided by Lawrence Venuti’s (1995) theoretical framework of domestication and foreignization, this study seeks to identify various cultural elements contained in the source text, analyze the strategies applied in their English translation, and evaluate how effectively these strategies preserve the original cultural meanings. The study employs a qualitative descriptive method, focusing on selected chapters that contain a high density of cultural expressions, including traditional customs, idioms, social values, and historical references. Each cultural element is analyzed to determine whether the translator adopts domestication, foreignization, or a hybrid approach in rendering it into English. The analysis reveals that Annie Tucker skillfully combines both strategies: she uses foreignization to retain the local flavor and authenticity of Indonesian culture, while applying domestication to make the text more understandable for global readers. The findings show that domestication and foreignization are applied complementarily to preserve Indonesian cultural identity while maintaining readability, reflecting Venuti’s (1995) view that cultural authenticity and accessibility can coexist in literary translation. This research contributes to the field of translation studies by demonstrating how Indonesian literary works can reach international audiences without losing their cultural essence.